2018
DOI: 10.1111/josh.12699
|View full text |Cite
|
Sign up to set email alerts
|

Children's Obesogenic Behaviors During Summer Versus School: A Within‐Person Comparison

Abstract: BACKGROUND: Evidence consistently shows children in the United States gain 3 to 5 times more weight during summer vacation (∼2.5 months) compared to the 9-month school year. The purpose of this study is to examine within-child differences in 4 obesogenic behaviors (physical activity [PA], sedentary/screen-time, diet, and sleep) during school versus summer. METHODS:We used a repeated-measures within-subjects design. Children (N = 30 mean age = 8.2 years; 57% female; 37% overweight/obese; 100% African American) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
54
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 44 publications
15
54
7
Order By: Relevance
“…To our knowledge only three studies have examined within-participant differences in obesogenic behaviors between the school year and summer vacation. Even though these studies were relatively small, ranging from 14 to 89 participants, all found that children increased time sedentary over summer vacation (21,22,58), consistent with the current study. The two studies that examined changes in diet during the summer vacation produced mixed findings (22,58).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…To our knowledge only three studies have examined within-participant differences in obesogenic behaviors between the school year and summer vacation. Even though these studies were relatively small, ranging from 14 to 89 participants, all found that children increased time sedentary over summer vacation (21,22,58), consistent with the current study. The two studies that examined changes in diet during the summer vacation produced mixed findings (22,58).…”
Section: Resultssupporting
confidence: 87%
“…Even though these studies were relatively small, ranging from 14 to 89 participants, all found that children increased time sedentary over summer vacation (21,22,58), consistent with the current study. The two studies that examined changes in diet during the summer vacation produced mixed findings (22,58). One study found that children ate more fruit during the summer vacation (22) while the other found the opposite (58).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Nonetheless, these are highly regulated contexts and can include restrictions such as heights for climbing that have a focus on injury prevention rather than children's engagement in play (Brussoni, Olsen, Pike, & Sleet, 2012;Van Rooijen & Newstead, 2017). Focus on these contexts alone is also not sufficient as research has started to reveal that children put on more weight during vacation periods (Von Hippel, Powell, Downey, & Rowland, 2007) and engage in more sedentary behaviours (Brazendale et al, 2018).…”
mentioning
confidence: 99%